Pengaruh Komunikasi, Disiplin, Pengembangan Karir, dan Motivasi Kerja terhadap Kinerja Karyawan PT XYZ - Ranisah, Fitria; Oktiani, Friska; Rutmaya, Rutmaya; Sumbogo, Ignatius Ario (UNIVERSITAS KALBIS, 2025)
This study aims to determine the effect of communication, discipline, career development, and work motivation on employee performance at PT XYZ. This study uses a field research method with a quantitative approach. This research was conducted by the employee analyst unit of PT XYZ, with a population of 51 employees. The sampling method used is Non-Probablity sampling with saturated sampling with a total of 51 employees with data collection techniques using path analysis using SPSS version 25. The results of this study conclude that there is a positive and significant effect of communication on employee performance, there is a negative effect of Discipline on Employee Performance, there is a positive and significant effect of Career Development on Employee Performance, there is a positive and significant influence of Work Motivation on Employee Performance and simultaneously Communication, Discipline, Career Development, and Work Motivation have an influence on Employee Performance of PT XYZ.